PSYCHOLOGICAL EMPOWERMENT DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR: PERAN MEDIASI JOB CRAFTING PADA KARYAWAN PT. BANK NAGARI KANTOR PUSAT - Ihsan, Serli Rahmatul; Zona, Mega Asri (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to examine: (1) the effect of psychological empowerment on organizational citizenship behavior (2) the effect of psychological empowerment on job crafting (3) the effect of job crafting on organizational citizenship behavior (4) the effect of psychological empowerment on organizational citizenship behavior through job crafting. This research is quantitative research and is a causal research. The population of this study were all employees of PT Bank Nagari Head Office, namely 262 people. The total sample used was 158 people who were taken using cluster proportional random sampling technique. Data collection using a questionnaire with a Likert Scale. The analysis technique used with PLS (Partial Least Square) which is a structural equation model (SEM) analysis technique using SmartPLS 4 software. The results of data processing in this study indicate that: (1) psychological empowerment has a positive and significant effect on organizational citizenship behavior in employees of PT Bank Nagari Head Office (2) psychological empowerment has a positive and significant effect on job crafting in employees of PT Bank Nagari Head Office (3) job crafting has a positive and significant effect on organizational citizenship behavior in employees of PT Bank Nagari Head Office (4) psychological empowerment has a positive and significant effect on organizational citizenship behavior through job crafting in employees of PT Bank Nagari Head Office. Penelitian ini bertujuan untuk menguji: (1) pengaruh psychological empowerment terhadap organizational citizenship behavior (2) pengaruh psychological empowerment terhadap job crafting (3) pengaruh job crafting terhadap organizational citizenship behavior (4) pengaruh psychological empowerment terhadap organizational citizenship behavior melalui job crafting. Penelitian ini adalah penelitian kuantitatif dan merupakan penelitian kausal. Populasi dari penelitian ini adalah seluruh karyawan PT. Bank Nagari Kantor Pusat yaitu sebanyak 262 orang. Total sampel yang digunakan adalah sebanyak 158 orang yang diambil dengan menggunakan teknik cluster proportional random sampling. Pengumpulan data menggunakan kuesioner dengan Skala Likert. Teknik analisis yang digunakan dengan PLS (Partial Least Square) yang merupakan teknik analisis model persamaan struktural (SEM) dengan menggunakan software SmartPLS 4. Hasil pengolahan data pada penelitian ini menunjukkan bahwa : (1) psychological empowerment berpengaruh positif dan signifikan terhadap organizational citizenship behavior pada karyawan PT. Bank Nagari Kantor Pusat (2) psychological empowerment berpengaruh positif dan signifikan terhadap job crafting pada karyawan PT. Bank Nagari Kantor Pusat (3) job crafting bepengaruh positif dan signifikan terhadap organizational citizenship behavior pada karyawan PT. Bank Nagari Kantor Pusat (4) psychological empowerment berpengaruh positif dan signifikan terhadap organizational citizenship behavior melalui job crafting pada karyawan PT. Bank Nagari Kantor Pusat.